2002
DOI: 10.1111/j.1745-4549.2002.tb00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Retorting and Storage on Liquid Mass Transfer in Canned Skipjack (Katsuwonas Pelamis) Muscle

Abstract: Mass loss of precooked tuna muscle during retorting and storage in cans impacts cannery yield and throughput. Changes in moisture content and mass of frozen, thawed, precooked tuna muscle chunks, canned in water, were determined after retorting and through five weeks of subsequent storage. Canned tuna pieces were retorted to equivalent lethality (Fo‐value of four) for different time and temperature processes. Retorting at a lower temperature, longer time resulted in less mass loss than higher temperature, shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…The spores of Clostridium botulinum in low-acid products (pH > 4.6) can be destroyed at the F 0 of 3 min, but more severe conditions are still in need to control spoilage organisms. [18,19] Bell et al [9] studied the mass loss of precooked tuna muscle at the F 0 of 4 min during retorting and the storage in cans. Simpson et al [20] established a mathematical model for the thermal processing of seafood packed in retortable pouches at a minimum F 0 of 4.5 min.…”
Section: Thermal Sterilization Of Sscmentioning
confidence: 99%
See 1 more Smart Citation
“…The spores of Clostridium botulinum in low-acid products (pH > 4.6) can be destroyed at the F 0 of 3 min, but more severe conditions are still in need to control spoilage organisms. [18,19] Bell et al [9] studied the mass loss of precooked tuna muscle at the F 0 of 4 min during retorting and the storage in cans. Simpson et al [20] established a mathematical model for the thermal processing of seafood packed in retortable pouches at a minimum F 0 of 4.5 min.…”
Section: Thermal Sterilization Of Sscmentioning
confidence: 99%
“…The effects of thermal sterilization on the final qualities of SSC products, including fish texture as well as sauce color and rheological properties, were compared at 110, 115, 121, and 130 • C at the same F 0 value of 4.5 min (recommend F 0 range for canned fish products: 4-6 min). [9] MATERIALS AND METHODS…”
Section: Introductionmentioning
confidence: 99%
“…As expected, all process combinations resulted in mass loss, which is in line with results obtained by other authors for single variables of interest (salt or retort process). The work of Bell and others (2002) is the most similar to this study, but it was made with tuna muscle, they did not specify the precooking step and salt addition. They reported a mass loss of 17% (which was assessed from a graph, not reported as a number) considering just the retort step.…”
Section: Resultsmentioning
confidence: 98%
“…However, this heat treatment also denatures the protein in the mussel meats releasing water from the soluble proteins and lipids that are expelled from the mussel tissue (Kramer and Szczesniak 1973; Leander and others 1980; Skipnes and others 2002). Bell and others (2002) studied the precooking process on tuna muscle destined for canning, concluding that reduction in muscle mass impacted productivity of the tuna canning industry. Thus, precooking is a process most important to product quality and industrial productivity (Lassen 1965; Chai and others 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The thermal treatment that is delivered to the food packed inside the container results in the changes that have both positive and negative effects on various sensory and nutritive qualities. Bell et al (2002) reported that a process temperature greater than 100C results in physicochemical changes that affect the final quality and yield of a canned product. Whether the effect is beneficial or harmful, it is primarily reflected on the sensory attributes of the food of which the easily perceived ones are the color and texture.…”
Section: Introductionmentioning
confidence: 99%